CSU prof wins top-notch prize: Rolston, 'father of environmental ethics,' plans trip to Buckingham Palace - Jones, Rebecca, author; Rocky Mountain News, publisher (Colorado State University. Libraries, 2003)
Interview citing Dr. Rolston's career and contributions to the study of nature, environmental ethics, and the relationship between science and religion.
Keywords: philosophy professor; Rolston, Holmes, 1932-2025; Templeton Prize; Colorado State University